Proliferation And Prognostic Biomarkers In Colorectal Cancer (Texas Journal of Medical Science, 2025)
Colorectal cancer (CRC) is a major cause of morbidity and mortality worldwide. Despite advances in diagnosis and therapy, CRC remains a heterogeneous disease with diverse clinical outcomes. A growing body of evidence suggests that tumor proliferation dynamics and associated molecular alterations play critical roles in disease progression, recurrence, and treatment response. This review summarizes recent progress in understanding proliferation-related biomarkers in CRC, emphasizing the prognostic and predictive value of immunohistochemical and molecular indicators. Classical proliferation markers such as Ki-67, PCNA, and cyclins are discussed alongside genetic and epigenetic alterations including APC, KRAS, TP53 mutations, microsatellite instability (MSI), chromosomal instability (CIN), and CpG island methylator phenotype (CIMP). The integration of immunohistochemistry with next-generation sequencing and RNA profiling has enabled identification of novel prognostic factors, including non-coding RNAs and methylation signatures. Understanding these markers enhances risk stratification and supports the development of personalized treatment approaches in colorectal cancer management.